Assessment of Knowledge and Physical Activity Pattern of Civil Servants in Ilorin South Local Government, Kwara State, Nigeria - Adewale Adeoye; Yusuf Naimat Aderonke; Abubakar Nurudeen Ojo (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
If regular physical activity can be packaged into a pill, it will be the commonest drug on the counter. Therefore, this study assessed the knowledge and physical activity pattern of civil servants in Ilorin south Local Government, Kwara State, Nigeria. Descriptive research design of survey method was used for this study. The population for this study comprised civil servants in Ilorin South Local Government, Kwara State, Nigeria. Multi-stage probability sampling technique was conducted to select 259 respondents. Adapted GPAQ was used as instrument for data collection. The instrument was validated and tested for reliability. A correlation co-efficient of 0.84 was obtained through test re-test method using Pearson Product Moment Correlation. Socio-demographic data of the respondents was analysed using descriptive statistics of frequency, percentage, mean and standard deviation and to answer the research questions; inferential statistics of Pearson’s Product Movement Correlation (PPMC), One-way Analysis of variance (ANOVA) and independent sample t-test were used to test the null hypotheses at 0.05 significance. It was concluded in the study that there is significant relationship on Knowledge and pattern of physical activity of civil servants in Ilorin South Local Government Kwara State among others. Recommendation this study; experts in the field of physical activity and fitness in conjunction with the management of various ministries and commissions in the study locale should organise workshops and seminars to improve the knowledge of the civil servants on the benefits of regular participation in physical activity. Also, an official hour should be earmarked for staff to encourage participation by all.